(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
This study examines the critical importance of audio design in crafting immersive experiences within the metaverse. The analysis focuses on key technologies driving this field, with particular emphasis on spatial audio techniques such as Head-Related Transfer Functions (HRTF) and Ambisonics, which enable precise three-dimensional sound positioning. The research investigates adaptive audio rendering, highlighting tools such as Microsoft’s Spatial Audio Unity Plugin, which facilitates dynamic soundscape adjustments based on user interactions. Furthermore, the application of artificial intelligence in audio design is explored, with a discussion on the potential of Generative Adversarial Networks (GANs) for synthetic sound production and personalized audio experiences. The study presents two significant case studies: the partnership between TCG World, STYNGR, and Downtown for interactive sonic environments, and research on Audio Augmented Reality (AAR) in art galleries. Ethical considerations, including privacy, accessibility, and the psychological impact of immersive audio, are critically examined. The research concludes by exploring future directions, such as cross-modal integration and emotional AI systems in metaverse audio design, emphasizing the necessity for responsible development practices. Through this comprehensive analysis, the study aims to provide insights into the challenges and opportunities presented by audio design in virtual environments, contributing to the evolving landscape of metaverse technology.